Chronic respiratory failure due to toxic epidermal necrosis in a 10 year old girl. Issue 1 (February 2015) - Thimmesch, M.; Gilbert, A.; Tuerlinckx, D.; Bodart, E.
<x content-type="archive" xml:space="preserve">Abstract</x> Toxic epidermal necrosis is a severe mucocutaneous disease with a high mortality rate. A third of the patients surviving the acute phase will develop pulmonary complications. The most frequent complication is bronchiolitis obliterans. Despite well-conducted treatment, in most cases, lung injury often leads to chronic respiratory failure. We describe here the case of a young patient that presented a toxic epidermal necrosis at the age of 3 years. Poor therapeutic compliance result in chronic respiratory failure and after 7 years of follow-up, pulmonary transplant remains the only long-term alternative. Close monitoring of respiratory symptoms in the course of toxic epidermal necrosis, intense treatment as soon as they appear and a long-term follow-up are essential to postpone chronic respiratory failure.